Design and Parameter Optimization of Fresh Chili Seed Extractor - Jing Bai; Xingye Chen; Weiquan Fang; Huimin Fang; Xinzhong Wang (Agriculture)
There is a poor mechanization level among the existing chili seed extractors. The separation operation still relies on manual labor, with low efficiency and high costs. In this study, a fresh chili seed extractor for small-scale operations was designed, and the relevant parameters were optimized. The rotational speed of the drum, feeding speed, sieve diameter, threshing gap, number of peg teeth, and inclination angle of the frame were used as test factors, and the comprehensive score (loss rate, crushing rate, and impurity rate) of the effect of the chili seed extractor was set as an evaluation index. The initial parameters were selected via the Plackett–Burman test. The steepest climb test was carried out to determine the ranges of significance for the parameters. Moreover, a Box–Behnken test were conducted to obtain the optimal parameter combination: the drum rotation speed was 661 r/min, the sieve diameter was 8.5 mm, and the disengagement gap was 9.4 mm. The test results showed that the loss rate was 3.83%, the crushing rate was 2.01%, and the impurity rate was 11.31%, which met the actual production requirements for chili seeds. This study is expected to provide a necessary reference for the design of chili seed extractors.